The Impact of Early Social Interactions on Later Language Development in Spanish–English Bilingual Infants. Issue 4 (19th October 2016) - Ramírez‐Esparza, Nairán; García‐Sierra, Adrián; Kuhl, Patricia K.
Abstract : This study tested the impact of child‐directed language input on language development in Spanish–English bilingual infants ( N  =   25, 11‐ and 14‐month‐olds from the Seattle metropolitan area), across languages and independently for each language, controlling for socioeconomic status. Language input was characterized by social interaction variables, defined in terms of speech style ("parentese" vs. standard speech) and social context (one‐on‐one vs. group). Correlations between parentese one‐on‐one and productive vocabulary at 24 months ( n  =   18) were found across languages and in each language independently. Differences are highlighted between previously published monolingual samples, which used the same methods as the current study of bilingual infants. The results also suggest cultural effects on language input and language development in bilingual and bicultural infants.